Konstruksi Berita Pencalonan Prabowo Subianto dan Gibran Rakabuming Raka sebagai Capres dan Cawapres 2024 : Analisis Framing Pada Media Kompas.com dan CNN Indonesia (Edisi 16-25 Oktober 2023) - Mareta Ushwatun Hasanah; Wahyu Widiastuti; Andy Makhrian (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
On 25 October 2023, Prabowo Subianto and Gibran Rakabuming Raka officially registered with the General Election Commission as Presidential and Vice-Presidential candidates. Therefore, the researcher wants to know how the framing of the news media related to this. The media selected for this analysis are Kompas.com and CNNIndonesia. This study uses the framing method by Zhongdang Pan and Gerald M. Kosicki and uses the constructivism paradigm. The news data taken for this study were collected in the period 16-25 October 2023. Based on the results of the study, there was one news on Kompas.com that didn’t meet the 5W+1H elements and the comparison in the two news portals led to differences where Kompas.com media focused on the opinions of sources related to the advantages and chances of Gibran’s victory, and CNNIndonesia showed how the results of the electability data of the pair Prabowo and Gibran to win the 2024 Presidential Election.